THE ROLE OF INFLUENCER MARKETING IN BUILDING CONSUMER TRUST: A SYSTEMATIC LITERATURE REVIEW - M Rahul Firmansyah; Muhammad Aldi Losa; Robi Yahya (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to systematically examine the role of influencer marketing in building consumer trust within the context of digital marketing. The rapid growth of social media has transformed marketing strategies, positioning influencers as key opinion leaders who shape consumer perceptions and purchasing behavior. Consumer trust has become a critical factor, particularly in an environment characterized by information overload and skepticism toward conventional advertising. This research adopts a qualitative approach using the Systematic Literature Review (SLR) method to synthesize findings from 15 national journal articles published between 2023 and 2026. The selected studies focus on influencer marketing, influencer credibility, consumer trust, and consumer behavior, including purchase intention, purchase decision, loyalty, and repurchase intention. The results of the review indicate that influencer marketing plays a significant role in building consumer trust, primarily through influencer credibility, authenticity of content, and congruence between influencers and brands. Consumer trust is consistently identified as a key mediating or moderating variable that explains how influencer marketing affects consumer behavior. Furthermore, the findings highlight that influencer marketing is particularly effective among Generation Z consumers, who actively rely on social media influencers as sources of information and recommendations. This study contributes to the digital marketing literature by emphasizing consumer trust as the central mechanism underlying the effectiveness of influencer marketing. Practically, the results suggest that companies should prioritize long-term trust-building strategies by selecting credible influencers and creating authentic, value-driven content to enhance sustainable consumer relationships.